Remote reading of electricity meters using PLC - Negin Ahmadi; Zahra Khajenasir Jahromi (Institute of Advanced Engineering and Science, 2020)
The telecommunications platforms of the electricity industry, including optical fiber, wireless, radio and microwave, despite providing sufficient bandwidth to transmit power market data, have limitations and disadvantages that are particularly apparent in remote suburban areas. PLC technology provides such facilities relatively. So this paper aim is providing practical solutions for the transmission of electricity market meters data through this type of PLC. This paper examines how to transfer the data from the electricity market to the central server using a PLC telecommunications platform and a practical example at 132 kV. In this case, the appropriate option is PLC. In this paper, it has been shown that there is the possibility of sending market data onto the PLC platform in transient and over- voltage transmission lines, which so far seemed to be impractical. With the comprehensive implementation of this work in the country's electricity industry, especially regional electricity, a major step will be taken to create a smart grid for meter readings. Due to the successful outcome of the experiment, it is possible to easily connect the PLC, the availability of this platform in many posts, a large and new smart grid for reading electricity meter readings.